2016
DOI: 10.1016/j.phrp.2016.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Emotional Intelligence among Nursing and Medical Students

Abstract: ObjectivesThe purpose of this study is to identify the types of perception of emotional intelligence among nursing and medical students and their characteristics using Q methodology, and to build the basic data for the development of a program for the would-be medical professionals to effectively adapt to various clinical settings in which their emotions are involved.MethodsData were collected from 35 nursing and medical students by allowing them to classify 40 Q statements related to emotional intelligence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…This has resulted in a renewed focus on developing student empathy, caring, and compassion, and a concerted effort to develop students' emotional intelligence through curriculum redesign. A study that examined whether emotional intelligence affected academic achievements found that flexibility in dealing with life situations can be a better predictor of students' post-graduation success than grade point average [12][13][14].…”
Section: Developing Emotional Intelligence To Enhance Academic Achievmentioning
confidence: 99%
“…This has resulted in a renewed focus on developing student empathy, caring, and compassion, and a concerted effort to develop students' emotional intelligence through curriculum redesign. A study that examined whether emotional intelligence affected academic achievements found that flexibility in dealing with life situations can be a better predictor of students' post-graduation success than grade point average [12][13][14].…”
Section: Developing Emotional Intelligence To Enhance Academic Achievmentioning
confidence: 99%
“…Hal ini dibuktikan oleh Freshwater & Stickley (2009), pada mahasiswa perawat kecerdasan emosional terbentuk pada masa perawat tersebut masih menjadi mahasiswa. Selain itu juga terdapat penelitian pada mahasiswa kedokteran dan keperawatan di Korea yang menemukan bahwa kecerdasan emosional akan terus berkembang seiring dengan tingkatan mahasiswa di kampusnya (Chun & Park, 2016). Mayer, Salovey, Caruso, & Sitarenios (2006) menjelaskan bahwa kecerdasan emosional dalam pribadi mahasiswa kesehatan terbukti memiliki andil yang besar dalam kemampuan menyelesaikan masalah (Problem Solving Skill).…”
Section: Pendahuluanunclassified
“…Cross-cultural studies of emotional intelligence are extremely scarce, because in most cases this phenomenon is investigated for its impact on learning or management processes in various practical applications (Chun and Park, 2016). Nevertheless, the results achieved demonstrate similarity to those already obtained earlier in other works.…”
Section: Discussionmentioning
confidence: 99%